Knowledge, attitudes and practices of Iranian people about food safety and hygiene during covid-19 pandemic - Ali Salehi; Fatemeh Salmani; Ensiyeh Norozi; Parisa Sadighara; Tayebeh Zeinali (BMC, 2022)
Abstract Aim The objective of this study was to develop a cultural adopted questionnaire for evaluation of knowledge (K), attitude (A) and practice (P) of Iranian population toward food safety during Covid-19. Methods The study is based on an online questionnaire that filled by 712 Iranians over 16 years old. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and reliability assessment were performed. The construct validity of A and P determined by EFA and confirmed by CFA. Difficulty index was used for K. Results The reliability score of questionnaire was satisfactory. The three items of K-A-P questionnaire were significantly associated with the total score of questionnaire. The KAP questionnaire regarding food safety in covid-19 consisted of 27 items multidimensional scale with strong psychometric features. The respondent showed a satisfactory level of KAP during covid-19 pandemics. Conclusion The KAP questionnaire regarding food safety in covid-19 is a valid and reliable tool for measurement of knowledge, attitude and practice of people regarding food safety in covid-19.